The implementation low carbon cities framework (LCCF) of local authority in development control towards green cities / Siti Kartina Juhari ... [et al.] - Juhari, Siti Kartina; Omar, Dasimah; Kamarudin, Siti Mazwin; Mat Noor, Mohd Sallehuddin (2019)
Low Carbon, low emission or even carbon-neutral cities contribute significantly towards sustainability. The low-carbon green city refers to a city that is ecologically low in CO2 emission, uses energy and environmental technologies to eliminate CO2 emission. This paper aims to investigate the LCCF implementation in local authorities. The objectives of the paper are to study the implementation by selected local authorities for further improvement of the LCCF Checklist. The methodology of this study was qualitative data analysis with NVivo. The article only focuses on Selangor Local Authorities. The finding of this research is Local Authority plays a major role in manifesting the LCCF Checklist in development control. The LCCF Checklist must be incorporated in the Development Proposal Report (LCP), an incentive to the developer and monitoring the implementation of the LCCF Checklist from the federal and state level.